Pengaruh Penerapan Metode Storytelling Berbasis SAVI untuk Meningkatkan Daya Ingat Siswa Mata Pelajaran Akidah Akhlak di MA Salafiyah Merakurak - Nikmatul Asiyah; Sani Latifatul Khilmina (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research aims to investigate the implementation of the storytelling method based on SAVI in Akidah Akhlak learning at MA Salafiyah Merakurak. This study employs a quantitative approach with a one-group pretest-posttest design, involving class X students as subjects. It utilizesdata collection techniques that include pretests, posttests, observations, and documentation. Data analysis was conducted using descriptive statistics and a dependent t-test to measure the effect of the treatment on students' memory retention. The research findings indicate that the application of the SAVI-based storytelling method successfully enhanced students' engagement and memory retention in Akidah Akhlak learning. Students demonstrated greater focus, enthusiasm, and active involvement during the learning process. The integration of various learning modalities (somatic, auditory, visual, and intellectual) helped students comprehend abstract akidah concepts more meaningfully. The average memory retention score significantly improved from the